Enhancement of thermoelectric properties of Yb0.25Co4Sb12 skutterudites through Ni substitution - Ali Bashir, Mohamed Bashir; Suhana Mohd Said,; Mohd Faizul Mohd Sabri,; Yuzuru Miyazaki,; Dhafer Abdul Ameer Shnawah,; Masanori Shimada,; Mohamed Hamid Elsheikh, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this work, we investigate the effects of Ni doping on the thermoelectric (TE) properties of Yb0.25Co4Sb12 sample. Yb0.25Co4-xNixSb12 (0 ≤ x ≤ 0.5) samples were prepared by mechanical alloying and subsequently consolidated by spark plasma sintering. The morphology of consolidated samples were characterized by X-ray diffraction (XRD) and scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM-EDS). The thermoelectric properties of bulk samples were measured from room temperature to 800 K. The XRD analysis confirmed that, the successful formation of the Co4Sb12 skutterudite phase and Ni is substituted into Co site of the skutterudite crystal lattice. Moreover, the electrical resistivity decreased to 14.6 μΩm at 785 K for Yb0.25Co3.5Ni0.5Sb12 sample, due to increase of the electron concentration by Ni-addition. The absolute Seebeck coefficient reached the highest value of 223 μV/K at 592 K for Yb0.25Co3.7Ni0.3Sb12 sample, thus yielding a maximum value of power factor of 2.41 × 10-3 W/mK2 at 592 K. The highest dimensionless thermoelectric figure of merit value ZT of 0.49 at 692 K has been achieved for the Yb0.25Co3.7Ni0.3Sb12 sample, compared to ZT=0.06 for the Yb0.25Co4Sb12 sample at same temperature. This work indicates a strategy to improve the thermoelectric performance by Ni substitution of Co sites in the Yb0.25Co4Sb12 skutterudite through simultaneous improvement of its electrical conductivity, Seebeck coefficient and reduction of its thermal conductivity.